Treatment of Immunocompromised, Critically Ill Patients with Influenza A H1N1 Infection with a Combination of Oseltamivir, Amantadine, and Zanamivir - Wouter J. Meijer; Wiete Kromdijk; Marcel P. H. van den Broek; Pieter-Jan A. Haas; Monique C. Minnema; Charles A. Boucher; Dylan W. de Lange; Annemarie M. J. Wensing (Case Reports in Infectious Diseases)
Immunocompromised patients are at increased risk of complications of influenza virus infection. We report on two critically ill patients on immunosuppressive medication with influenza pneumonia. In both patients, oseltamivir monotherapy did not result in clearance of the virus after 18 and five days, respectively. After adding zanamivir and amantadine to the treatment, PCRs on pharyngeal and/or plasma specimens turned negative in both patients after four and three days, respectively. We suggest, that in critically ill patients with influenza A H1N1 infection, treatment efficacy should be monitored closely and treatment with a combination of antiviral drugs should be considered.